Correlation of film morphology and defect content with the charge-carrier transport in thin-film transistors based on ZnO nanoparticles - Polster, Sebastian; Jank, Michael; Frey, Lothar (Journal of Applied Physics, 2016)
The correlation of defect content and film morphology with the charge-carrier transport in field-effect devices based on zinc oxide nanoparticles was investigated. Changes in the defect content and the morphology were realized by annealing and sintering of the nanoparticle thin films. Temperature-dependent electrical measurements reveal that the carrier transport is thermally activated for both the unsintered and sintered thin films. Reduced energetic barrier heights between the particles have been determined after sintering. Additionally, the energetic barrier heights between the particles can be reduced by increasing the drain-to-source voltage and the gate-to-source voltage. The changes in the barrier height are discussed with respect to information obtained by scanning electron microscopy and photoluminescence measurements. It is found that a reduction of surface states and a lower roughness at the interface between the particle layer and the gate dielectric lead to lower barrier heights. Both surface termination and layer morphology at the interface affect the barrier height and thus are the main criteria for mobility improvement and device optimization. (C) 2016 AIP Publishing LLC.